Sequential injection methodology for carbon speciation in bathing waters - Santos, Inês C. (2014)
A sequential injection method (SIA) for carbon speciation in inland bathing waters was developed comprising, in a single manifold, the determination of dissolved inorganic carbon (DIC), free dissolved carbon dioxide (CO2), total carbon (TC), dissolved organic carbon and alkalinity. The determination of DIC, CO2 and TC was based on colour change of bromothymol blue (660 nm) after CO2 diffusion through a hydrophobic membrane placed in a gas diffusion unit (GDU). For the DIC determination, an in-line acidification prior to the GDU was performed and, for the TC determination, an in-line UV photo-oxidation of the sample prior to GDU ensured the conversion of all carbon forms into CO2. Dissolved organic carbon (DOC) was determined by subtracting the obtained DIC value from the TC obtained value. The determination of alkalinity was based on the spectrophotometric measurement of bromocresol green colour change (611 nm) after reaction with acetic acid. The developed SIA method enabled the determination of DIC (0.24-3.5 mg C L-1), CO2 (1.0-10 mg C L-1), TC (0.50-4.0 mg C L-1) and alkalinity (1.2-4.7 mg C L-1 and 4.7-19 mgC L-1) with limits of detection of: 9.5 mu g C L-1, 20 mu g C L-1, 0.21 mg C L-1, 0.32 mg C L-1, respectively. The SIA system was effectively applied to inland bathing waters and the results showed good agreement with reference procedures.